2019
DOI: 10.1186/s42269-019-0120-z
|View full text |Cite
|
Sign up to set email alerts
|

Advances in quantifying soil organic carbon under different land uses in Ethiopia: a review and synthesis

Abstract: Background: In the face of climate change and global warming, scientists globally are striving for effective techniques on how best to sequester carbon in order to reduce global warming and achieve environmental sustainability. This paper reviews the available literature on the influence of various land use changes on gains and/ or losses of soil carbon (C) stocks in Ethiopia. Results: Our review indicated that 33.3% of the studies reported soil organic carbon (SOC) concentration, 13.9% reported only SOC stock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 119 publications
(169 reference statements)
1
4
0
Order By: Relevance
“…Many leguminous tree species contribute to higher soil organic carbon and nitrogen stocks. These results corroborate the findings by Okolo et al (2019), who showed higher soil carbon in forests than in deforested lands. Furthermore, the low carbon stocks in the deforested sites may be due to leaching and surface erosion losses.…”
Section: ____________________________________________________________...supporting
confidence: 92%
See 1 more Smart Citation
“…Many leguminous tree species contribute to higher soil organic carbon and nitrogen stocks. These results corroborate the findings by Okolo et al (2019), who showed higher soil carbon in forests than in deforested lands. Furthermore, the low carbon stocks in the deforested sites may be due to leaching and surface erosion losses.…”
Section: ____________________________________________________________...supporting
confidence: 92%
“…This research is in line with Tashi (2017), who found that the wood roots buried in the soil after deforestation decay steadily and continue to improve the organic matter content of the soil. Also, Okolo et al (2019) projected the organic carbon and nitrogen stocks in the forested and deforested sites in the range between 230 Mg ha -1 and 65 Mg ha -1 , respectively.…”
Section: ____________________________________________________________...mentioning
confidence: 99%
“…This could be attributed to the significant conversion of forestlands (-1.16%, -4.23%), grasslands (−1.31%, −3.26%) and shrublands (−2.41%, −3.59%) to other land uses, mainly croplands (Table S3) and extractive nature of the farming practice. In line with this, Negasa et al [72] and Okolo et al [73] indicated that conversion of native forest to other land uses and the intensification of agricultural activities resulted in a significant decrease in the SOC stocks across Ethiopia.…”
Section: Soil Organic Carbon Lossmentioning
confidence: 76%
“…Low BD in natural (forests) and semi-natural (exclosures) ecosystems, could be attributed to constant input of high soil organic residues on the upper layer of the soil [83][84][85][86] . The contribution of tree roots to the subsoil organic matter (OM) accumulation, including root litter decomposition leads to the decrease in BD in forests [87][88][89] .…”
Section: Discussionmentioning
confidence: 99%